Visions and Recommendations for By the IUCN Commission on Education and Communication (CEC) - Czippan, Katalin; Cheryl, Charles; Abd-Alhad, Firas; Abdallah, Aishah; Zavarzin, Aleksey; Pisupati, Balakrishna; Sziva, Daniel; Li, Hanying; Camargo, Luis; Ratiani, Manana; Otieno, Margaret; Garnett, Tommy; et al. (IUCN Commission on Education and Communication, 2022)
Since its birth in 1949 the IUCN CEC has embraced an active advocacy for promoting education as a means to adopt attitudes and practices leading to nature conservation and human well-being. Against this target the UNESCO Futures of Education initiative resonates with the CEC in the quest for a knowledge-based education that forges a better future for humankind and Earth. The CEC and its partners in #NatureForAll movement have embarked on reconnection with nature as an evidenced approach to ensure a prosperous and sustainable coexistence of humanity and nature and found that education in both its formal and creative techniques should work on reestablishing these connections. In response to the UNESCO Futures of Education initiative the CEC conducted a two phase consultation process (guided by the minimally modified UNESCO survey on the top challenges and purposes of education) to explore its members’ views on which challenges are expected to most affect humankind in 2050 and are thus worth addressing in education directed at sustainable development. The process also included drawing members’ recommendations on how education in the fields of nature, biodiversity and sustainability can contribute in meeting these challenges. It may not be considered a surprise that among the top five challenges selected by the respondents the first four places were occupied by nature-related challenges namely climate change, biodiversity loss, environmental crises and human-nature disconnect, with this latter being added to the survey list in light of respondents’ relevant backgrounds and experiences. Several respondents who chose these challenges also selected other challenges that are not so distinctly related to nature issues thus pinpointing associations between the two types such as cause-effect relations. Hence we see economic inequalities, global health crises, poverty and injustice also significantly chosen as top five challenges. In voting for issues education should focus on to meet the top five challenges (the above four and population growth) the overwhelming majority of respondents cited systemic change and sustainability through knowledge transfer, problem solving, attitude change and promotion of active and conscious citizenship. Education, many respondents argued, should focus on behavioural change of students, adults and decision makers. It should also mainstream locality considerations such as the revival of traditional knowledge, be based on firsthand learning in natural settings and follow innovative approaches. Combating climate change, which was considered the top challenge, 2 exemplifies this emphasis on local knowledge transfer, place-based engagement, innovative education methods, systemic and critical thinking as to create awareness, change attitudes and develop skills to act effectively against its impact and best serve the education purposes necessary to minimize this impact on humankind and Earth in 2050.